Brain Structural Covariance Network Topology in Remitted Posttraumatic Stress Disorder - Sun, Delin; Davis, Sarah L.; Haswell, Courtney C.; Swanson, Chelsea A.; , Mid-Atlantic MIRECC Workgroup; LaBar, Kevin S.; Fairbank, John A.; Morey, Rajendra A.; Beckham, Jean C.; Brancu, Mira; Calhoun, Patrick S.; Dedert, Eric; et al. (Frontiers in Psychiatry, 2018)
Posttraumatic stress disorder (PTSD) is a prevalent, chronic disorder with high psychiatric morbidity; however, a substantial portion of affected individuals experience remission after onset. Alterations in brain network derived from cortical thickness correlations are associated with PTSD, but the effects of remitted symptoms on network topology remain essentially unexplored. In this cross-sectional study, US military veterans (N=317) were partitioned into three diagnostic groups, current PTSD (CURR-PTSD, N=101), remitted PTSD with lifetime but no current PTSD (REMIT-PTSD, N=35), and trauma-exposed controls (CONTROL, n=181). Cortical thickness was assessed for 148 cortical regions (nodes) and suprathreshold interregional partial correlations across subjects constituted connections (edges) in each group. Four centrality measures were compared to characterize between-group differences. The REMIT-PTSD and CONTROL groups showed greater centrality in left frontal pole than the CURR-PTSD group. The REMIT-PTSD group showed greater centrality in right subcallosal gyrus than the other two groups. Both REMIT-PTSD and CURR-PTSD groups showed greater centrality in right superior frontal sulcus than CONTROL group. The centrality in right subcallosal gyrus, left frontal pole and right superior frontal sulcus may play a role in remission, current symptoms and PTSD history, respectively. The network centrality changes in critical brain regions and structural networks are associated with remitted PTSD, which typically coincides with enhanced functional behaviors, better emotion regulation, and improved cognitive processing. These brain regions and associated networks may be candidates for developing novel therapies for PTSD. Longitudinal work is needed to characterize vulnerability to chronic PTSD, and resilience to unremitting PTSD.